Pengaruh Customer Experience, Keamanan, dan Ketepatan Waktu Terhadap Kepuasan Pelanggan Shopee Express di Kota Bandung - Nasrul Abdul Aziz Taba; Indri Ferdiani Suarna (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Indonesia is the country with the fourth largest number of internet users in the world, after the United States, with 212.9 million users in 2023. The development of technology and the internet has had a significant impact on people's lives, especially in terms of online shopping. E-commerce users in Indonesia have increased significantly in recent years. Shopee is one of the platforms that is often used by Indonesians to shop online easily, safely, and quickly. This platform supports customers with strong payments and logistics services, and can be easily accessed via smartphones. Shopee Express, as part of Shopee's e-commerce service, has advantages over other platforms because of the various offers provided. However, a number of Shopee consumers have complained about the delivery service, ranging from damaged goods to packages that arrive late. This study aims to determine the effect of Customer Experience, Security, and Punctuality on Shopee Express Customer Satisfaction in Bandung City. This study uses a descriptive and verification approach with quantitative methods, and data collection techniques using questionnaires. Respondents' answers to the questionnaires distributed were then analyzed using research instrument analysis, classical assumption tests, and multiple linear regression. The statistical analysis tool used in this study is the Statistical Package for the Social Science (SPSS) software. The number of samples in this study was 385 people, selected through simple random sampling techniques. The results of multiple linear regression analysis show that partially, Customer Experience has an effect of 11.953, Security of 5.466, and Punctuality of 8.647, which have a positive and significant effect on Customer Satisfaction. Simultaneously, Customer Experience, Security, and Punctuality have a positive and significant effect on Customer Satisfaction of 389.559, with a coefficient of determination of 75.2%.